2008
DOI: 10.2337/db08-0054
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin-Like Transcript 3-Fc Suppresses T-Cell Responses to Allogeneic Human Islet Transplants in hu-NOD/SCID Mice

Abstract: OBJECTIVE-The aim of our study was to explore the immunomodulatory activity of soluble immunoglobulin (Ig)-like transcript (ILT) 3-Fc in pancreatic islet transplantation and to determine its mechanism of action.RESEARCH DESIGN AND METHODS-NOD/SCID mice in which diabetes was induced by streptozotocin injection were transplanted with human pancreatic islet cells. Mice in which the transplant restored euglycemia were humanized with allogeneic peripheral blood mononuclear cells and treated with ILT3-Fc or control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
67
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 41 publications
(50 reference statements)
8
67
0
Order By: Relevance
“…ILT3Fc-induced inhibition of IFN-g expression was found in all of our previous studies (9)(10)(11)(12) and is shown as a control for the ILT3Fc effect ( Fig. 2A).…”
Section: Induction Of Bcl6 Socs1 and Dusp10 By Ilt3fc Is 39-utr Depsupporting
confidence: 69%
See 2 more Smart Citations
“…ILT3Fc-induced inhibition of IFN-g expression was found in all of our previous studies (9)(10)(11)(12) and is shown as a control for the ILT3Fc effect ( Fig. 2A).…”
Section: Induction Of Bcl6 Socs1 and Dusp10 By Ilt3fc Is 39-utr Depsupporting
confidence: 69%
“…The strong immunosuppressive activity of ILT3Fc has been documented by its ability to suppress allograft rejection (10,11), a phenomenon in which myriads of MHC-bound peptides are recognized via the direct and indirect pathways, triggering rejection (45). Therefore, it is most likely that recognition of a limited number of autoantigenic, tissue-specific peptides can be inhibited by ILT3Fc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 In contrast, at least some of the inhibitory effects of LILRB4 may result from 'reverse signalling' through its T-cell ligand, as soluble forms of the receptor are sufficient to inhibit T-cell proliferation. 17,18 As evidenced by their nomenclature, LILRA2 and LIL-RA4 signal through ITAM motifs and might therefore be expected to exert 'activating' effects on the APC phenotype. Instead, LILRA4 negatively regulates the secretion of type I interferons by plasmacytoid DCs.…”
Section: The Influence Of Lilrs On Antigen-presenting Functionmentioning
confidence: 99%
“…LILRA2 engagement Involved in HLA-G-mediated allograft tolerance 49,94 Peripheral blood mononuclear cells from patients with systemic lupus erythematosus exhibit poor LILRB1 function and diminished expression of this receptor on B cells 58 Coexpressed with HLA-G in multiple sclerosis lesions 60 Up-regulated during HIV infection (see text for details) 63,64,95,96 Proportion of LILRB1 + B cells correlates with severity of malaria 70 Involved in HLA-G-mediated tumour immune evasion 38,[75][76][77]79 LILRB2 Up-regulated on DCs and ECs in the T-cell suppression cascade which generates allograft tolerance 13,23,41 Involved in HLA-G-mediated allograft tolerance 48,94 Up-regulated in rheumatoid arthritis, suggested role in spondyloarthritis 51,53 Up-regulated by interleukin-10 in HIV patients 27 Higher affinity for HIV-1 viral escape mutant 15 Expressed on B cells in leukaemia patients and tumour cells in lung cancer patients 72,73 Involved in HLA-G-mediated tumour immune evasion 38,[75][76][77]79 LILRB4 Up-regulated on DCs and ECs in the T-cell suppression cascade which generates allograft tolerance 13,23,41 Suppresses pancreatic islet allograft rejection in humanized NOD/SCID mice 17 Role in tumour cell evasion of host immune system 18,71 Expressed on B cells in leukaemia patients 72 DCs, dendritic cells; ECs, endothelial cells; HCMV, human cytomegalovirus; HIV, human immunodeficiency virus; HLA, human leucocy...…”
Section: The Influence Of Lilrs On Antigen-presenting Functionmentioning
confidence: 99%